PENGARUH KOMPETENSI, BUDAYA ORGANISASI, LINGKUNGAN KERJA TERHADAP MOTIVASI DAN KINERJA KARYAWAN - I Putu Wahyudi (Jurnal Manajemen dan Bisnis, 2013)
This study is bassed ob fact that human resources as doers of an organization havegot different attitudes and experience. The differences cause every individual in doingactivities in the organization to have different work abilities or performances as well. Thisstudy was conducted in PT Astra International, Tbk. Toyota Sales Operation of Denpasar orbetter known as AUTO 2000 of Denpasar. The research concerns the effect of Competence,Culture of Organization, Work Environment towards Motivation and EmployeesPerformance in service division of AUTO 2000 of Denpasar.The respondent of this study were taken from all employees in service division ofAUTO 2000 of Denpasar excluded the head departement. The number of the respondent were55 people both permanent workers and contract workers whose position were as instructor,service advisor, foreman, technician, toyota home service attendants, vallet and car washattendants. The data were taken using questionnaire consisting of question delivered directlyto them all to fill in. The data were analyzed to the test the hypothesis using Path Analysiswith AMOS program 20.0 version.Based on the result of the analysis the conclusion was drawn that there was asignificantly positive effect of Competence towards the Work Performance and Motivation tothe Work Performance. There was not significant positive effect of Competence towardsMotivation, The Culture of Organization to the Motivation, The Culture of the Organizationto the Work Performance, The Work Environment to Motivation and the Work Environmentto the Work Performance. The percentage of Competence, Culture of Organtization, WorkEnvironment towards Motivasion was 37,3 % meanwhile the effect of Competence, Culture ofOrganization, Work Environment and Motivation towards Work Performance was 60,9 %.The magnitude percentage effect of Competence variable, Culture of Organization, WorkEnvironment and Motivation towards Work Performance after Motivation variable indicatesthat Motivational variable is moderator variable.Keywords : Competence, Culture of Organization, Work Environment, Motivation andWork Performance.